Deleterious Impact of a Novel CFH Splice Site Variant in Atypical Hemolytic Uremic Syndrome - Schönauer, Ria; Seidel, Anna; Grohmann, Maik; Lindner, Tom H.; Bergmann, Carsten; Halbritter, Jan (Frontiers in Genetics, 2019)
Atypical hemolytic uremic syndrome (aHUS) is a heterogeneous disorder characterized by microangiopathic hemolytic anemia (MAHA), thrombocytopenia, and acute kidney failure (AKI). In about 50% of cases, pathogenic variants in genes involved in the innate immune response including complement factors CFH, CFI, CFB, C3, and membrane co-factor protein (MCP/CD46) put patients at risk for uncontrolled activation of the alternative complement pathway. As aHUS is characterized by incomplete penetrance and presence of additional triggers for disease manifestation, genetic variant interpretation is challenging and streamlined functional variant evaluation is urgently needed. Here, we report the case of a 27-year-old female without previous medical and family history who presented with confusion, petechial bleeding, and anuric AKI. Kidney biopsy revealed glomerular thrombotic microangiopathy (TMA). Targeted next generation sequencing identified a paternally transmitted novel heterozygous splice site mutation in the CFH gene (c.3134-2A>G; p. (Asp1045_Thr1053del)) which, resulted in a partial in-frame deletion of exon 20 as determined by cDNA analysis. On the protein level, the concomitant loss of 9 amino acids in the short consensus repeat (SCR) domain 18 of CFH includes a highly conserved cysteine residue, which is assumed to be essential for proper structural folding and protein function. Treatment with steroids, plasmapheresis, and the complement inhibitor eculizumab lead to complete hematological and clinical remission after several months and stable renal function up to six years later. In conclusion, genetic investigation for pathogenic variants and evaluation of their functional impact, in particular in the case of splice site variants, is clinically relevant and enables not only better molecular understanding but helps to guide therapy with complement inhibitors.